1975
DOI: 10.1111/j.1399-3054.1975.tb03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of the Medium Associated with Normal and Fusicoccin‐Induced Seed Germination

Abstract: Fusicoccin, a toxin stimulating cell enlargement and inducing proton extrusion in various plant tissues, has been shown to replace kinetin, gibberellic acid and red light in breaking seed dormancy. It also removes the inhibitory effect of abscisic acid. The present data also show that the stimulating effect of fucicoccin on embryo growth of decoated radish (Raphanus sativus L.) and maize (Zea mays) seeds and on the development of maize embryos is accompanied by an early, significant acidification of the medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…This idea is based on the finding that both H+ secretion and K+ uptake are inhibited by ABA along with the inhibition of germination while fusicoccin promotes all three processes in the presence or in the absence of ABA. Whereas the wall loosening action of fusicoccin via H+ secretion seems to be firmly established also in the case of seed germination (1,8,18,20), we feel that the presently available evidence with respect to the causal involvement of ion transport processes in the signal response chain of ABA is not equally conclusive. In preliminary experiments, we were unable to detect any significant H+ secretion by rape embryos normally germinating on water under conditions where fusicoccin induces strong medium acidification and enhances germination.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This idea is based on the finding that both H+ secretion and K+ uptake are inhibited by ABA along with the inhibition of germination while fusicoccin promotes all three processes in the presence or in the absence of ABA. Whereas the wall loosening action of fusicoccin via H+ secretion seems to be firmly established also in the case of seed germination (1,8,18,20), we feel that the presently available evidence with respect to the causal involvement of ion transport processes in the signal response chain of ABA is not equally conclusive. In preliminary experiments, we were unable to detect any significant H+ secretion by rape embryos normally germinating on water under conditions where fusicoccin induces strong medium acidification and enhances germination.…”
Section: Resultsmentioning
confidence: 73%
“…From the extensive work with radish seeds (1,8,18,20), it has been suggested that germination is controlled by H+-mediated cell wall loosening and K+ accumulation, both contributing to an increase in the capacity for water uptake. ABA is thought to inhibit germination by counteracting these ion fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…cell elongation and radicle protrusion (4,5,9,15,20). FC2, which is known to stimulate proton extrusion in higher plants (17), breaks the dormancy due to light conditions, high temperature (20), ABA (9, 15); it also stimulates the rate of germination (9, 15) and counteracts the inhibition of an osmoticum medium (20).…”
Section: Introductionmentioning
confidence: 99%
“…cell elongation and radicle protrusion (4,5,9,15,20). FC2, which is known to stimulate proton extrusion in higher plants (17), breaks the dormancy due to light conditions, high temperature (20), ABA (9,15); it also stimulates the rate of germination (9,15) and counteracts the inhibition of an osmoticum medium (20). The effect of FC is correlated to the stimulation of proton extrusion (15) and potassium uptake capacity (9,20) and to the hyperpolarization ofthe transmembrane electric potential (PD) (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation